Sykelig overvektiges erfaringer og utfordringer med å delta i en livsstil intervensjon, -et beskrivende design - Skyrud, Randi Vangen; Trollvik, Anne (Nordisk Tidsskrift for Helseforskning, 2019)
The experiences and challenges faced by morbid obese subjects when participating in lifestyle intervention, a descriptive design The aim of this study was to examine the experiences and challenges of the morbidly obese when participating in a long-term lifestyle intervention. The subjects, whom qualified as morbidly obese, participated for over a year in a group-based lifestyle intervention with ongoing treatments. A qualitative design was chosen to collect descriptive information throughout semi-structured interviews. There was a total of seven informants (male and female). Weight loss in the morbidly obese is typically achieved through conservative management and lifestyle intervention, with bariatric surgery reserved as a last option. Patients diagnosed with morbid obesity are often concerned about failing yet again after multiple attempts of weight loss. However, when guidance, education, and support from health professionals is provided in addition to active participation within a supportive group with other morbidly obese people, patients become reality-oriented and able to both initiate and sustain an effective lifestyle change.